Respostas

2014-06-28T22:35:41-03:00
-4x²+4x-1=0


Δ = b² - 4.a.c 
Δ = 4² - 4 . -4 . -1 
Δ = 16 - 4. -4 . -1 
Δ = 0

x = (-b +- √Δ)/2a
x' = (-4 + √0)/2.-4       x'' = (-4 - √0)/2.-4
x' = -4 / -8                  x'' = -4 / -8
x' = 0,5                       x'' = 0,5
2014-06-29T12:15:55-03:00
- 4x² + 4x - 1 + 0 = 0
- 4x² + 4x - 1 = 0

a = (- 4)             b = 4                 c = (- 1)

Δ = b² - 4 * a * c
Δ = 4² - 4 * (- 4) * (- 1)
Δ = 16 - 16
Δ = 0

Obs: Quando o delta (Δ) for zero (0), só há uma raiz.

x = - b ± √Δ
     _________
          2 * a
x = - 4 ± √0
     ________
       2 * (- 4)
x = - 4 ± 0
      ______
         - 8

x = - 4 
      - 8
x = 0,5

Resposta: 0,5